Exponentially suppressed cosmological constant with enhanced gauge symmetry in heterotic interpolating models. (3rd December 2019) - Itoyama, H; Nakajima, Sota
Abstract: A few 9D interpolating models with two parameters are constructed and the massless spectra are studied by considering compactification of heterotic strings on a twisted circle with a Wilson line. It is found that there are some conditions between radius R and Wilson line A under which the gauge symmetry is enhanced. In particular, when the gauge symmetry is enhanced to SO(18)× SO(14), the cosmological constant is exponentially suppressed. We also construct a non-supersymmetric string model that is tachyon-free in all regions of moduli space and whose gauge symmetry involves E_8 .